Presence of Human Papillomavirus and Epstein–Barr Virus, but Absence of Merkel Cell Polyomavirus, in Head and Neck Cancer of Non-Smokers and Non-Drinkers - Mulder, Frans J.; Klufah, Faisal; Janssen, Famke M. E.; Farshadpour, Farzaneh; Willems, Stefan M.; de Bree, Remco; zur Hausen, Axel; van den Hout, Mari F. C. M.; Kremer, Bernd; Speel, Ernst-Jan M. (Frontiers in Oncology, 2021)
Objective: determine the presence and prognostic value of human papillomavirus (HPV), Epstein-Barr virus (EBV), Merkel cell polyomavirus (MCPyV), and cell cycle proteins in head and neck squamous cell carcinoma (HNSCC) of non-smokers and non-drinkers (NSND). Methods: clinical characteristics and tumors of 119 NSND with HNSCC were retrospectively collected and analyzed on tissue microarrays. RNAscope in situ hybridization (ISH) was used to screen for the presence of HPV and MCPyV mRNA. Immunohistochemistry was performed for expression of p16 as surrogate marker for HPV, Large T-antigen for MCPyV, and cell cycle proteins p53 and pRb. Positive virus results were confirmed with polymerase chain reaction. For EBV, EBV encoded RNA ISH was performed. Differences in 5-year survival between virus positive and negative tumors were determined by log rank analysis. Results: all oropharyngeal tumors (OPSCC)(n=10) were HPV-positive, in addition to one oral (OSCC) and one nasopharyngeal tumor (NPSCC). The other three NPSCC were EBV-positive. MCPyV was not detected. Patients with HPV or EBV positive tumors did not have a significantly better 5-year disease free or overall survival. Over 70% of virus negative OSCC showed mutant-type p53 expression. Conclusion: in this cohort, all OPSCC and NPSCC showed HPV or EBV presence. Besides one OSCC, all other oral (n=94), hypopharyngeal (n=1), and laryngeal (n=9) tumors were HPV, EBV, and MCPyV negative. This argues against a central role of these viruses in the ethiopathogenesis of tumors outside the oro- and nasopharynx in NSND. So, for the majority of NSND with virus negative OSCC, more research is needed to understand the carcinogenic mechanisms in order to consider targeted therapeutic options.